Bank branch outreach and access to banking services toward financial inclusion: An experimental evidence - Sudarshan Maity; Tarak Nath Sahu (Rajagiri Management Journal (RAMJ), 2023)
Purpose - Both branch and automated teller machine (ATM) are playing a crucial role in banking coverage expansion in India. People prefer to go to an ATM for withdrawal of money rather waiting in a queue for hours at a branch. Without the existence of a full-fledged brick-and-mortar branch, ATM also plays an important role by providing basic banking services. In India, a significant part of the population is excluded from banking access. The present study aims to investigate how the branch and ATM penetration influence financial inclusion. Design/methodology/approach - The study covers the period from 2008-2009 to 2019-2020. With the application of Welch's t-test, a comparative study is being conducted between branch and ATM. Further, with the application of regression analysis, the study analyses how the branch and ATM network expansion influence financial inclusion. Findings - Though in recent times customers prefers to visit an ATM and its growth rate is higher than branches, the study found no significant differences between the growth of branch and ATM. Further, results of regression show both branches and ATMs have significant impacts on financial inclusion. Originality/value - In micro concept both have a common role in respect of service provided to customers. While in macro concept a list of specific services can be provided through branch level only. This study has a significant role, considering the importance of branches or ATMs and cost of installing a physical branch.
Keywords: 650; Financial inclusion; Commercial bank; Automated teller machine; Bank branch